*Curso virtual para docentes de inglés: una alternativa para la profesionalización - Hernández, Fanny; Kostina, Irina (Íkala, Revista de Lenguaje y Cultura, 2006)
This article describes the experiences related to the design of a virtual course in the context of the Virtual Campus of the Universidad del Valle (Colombia). The course is directed at in-service English teachers, at undergraduates and graduates whose English level corresponds to false beginner, or at teachers of other subjects who plan to teach English in the immediate future. Received: 17-04-06 / Accepted: 15-08-06 How to reference this article: Hernández, F. & Kostina, I. (2006). Curso virtual para docentes de inglés: una alternativa para la profesionalización. Íkala, 11(1), pp. 209 – 231.